Inhibition of growth of colorectal cancer patient-derived subcutaneous xenografts using combined Wnt signaling pathway inhibitor and 5‑fluorouracil - A. S. Goncharova; A. V. Galina; D. V. Khodakova; G. Yu. Egorov; A. Yu. Maksimov; E. N. Kolesnikov; E. F. Komarova; A. A. Kiblitskaya; E. V. Zaikina; L. Z. Kurbanova; M. V. Mindar (Исследования и практика в медицине, 2022)
Purpose of the study. Was to analyze antitumor efficacy of the XAV 939 Wnt signaling pathway inhibitor and its combination with 5 fluorouracil in subcutaneous xenografts derived from patients with colorectal cancer.Materials and methods. Antitumor efficacy of the agents and their combination was studied in xenografts derived from patients with colorectal cancer and subcutaneously implanted in immunodeficient Balb/c Nude mice. All animals with tumors were divided into 4 groups (n = 5): group 1 received 5 fluorouracil 25 mg/kg, group 2 – XAV 939 25 mg/kg, group 3–5 fluorouracil and XAV 939 combination at the same dosages, group 4 was control. Criteria for the efficacy of the tested agents and their combination included tumor growth rate and tumor growth inhibition rate (TGI %).Results. The mean volumes of xenografts and tumor growth rate in the group receiving a combination of 5 fluorouracil and XAV 939 were 335.2 ± 40.7 mm3 , being lower than the averages of xenografts in controls – 609.3 ± 69.5 mm3 (p < 0.05). The mean volumes of xenografts in the group receiving 5 fluorouracil monotherapy were 601.9 ± 45.5 mm3 , in the group with the XAV 939 monotherapy – 527.9 ± 258.6 mm3 . The highest TGI (44.99 %) was registered in the group receiving a combination of 5 fluorouracil and XAV 939.Conclusion. The study revealed the ability of combined XAV 939 Wnt signaling pathway inhibitor and 5 fluorouracil to inhibit the growth of subcutaneous xenografts derived from patients with colorectal cancer.